2018
DOI: 10.4236/oalib.1104454
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Horizontal Transfer of Housekeeping and Hydrocarbons Catabolism Genes in Bacterial Genus with Potential to Application in Bioremediation Process

Abstract: In silico analysis can be useful to infer about the horizontal gene transfer (HGT) as well as to deduce about the evolutionary relations of catabolic genes. In this study, we performed the analysis of two housekeeping genes (fabD and rpoD) and two catabolic genes (alkB and catA) from 12 bacterial genus usually founded in marine environments. Comparing the trees obtained from Bayesian Inference hypotheses of these genes with 16S rDNA sequences, we noted the topologies are different among housekeeping or catabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…3 and 4 some branches contained alkB/M and ladA genes originating from genomes belonging to distantly related phyla. The placement of phylogenetically diverse groups in one branch hint at horizontal transfer of these genes between microbial taxa [ 16 ]. Additionally, apart from the chromosomal type, both alkB/M and ladA genes have previously been reported to be also located on plasmids (OCT and pLW1071), corroborating their potential for horizontal transfer.…”
Section: Resultsmentioning
confidence: 99%
“…3 and 4 some branches contained alkB/M and ladA genes originating from genomes belonging to distantly related phyla. The placement of phylogenetically diverse groups in one branch hint at horizontal transfer of these genes between microbial taxa [ 16 ]. Additionally, apart from the chromosomal type, both alkB/M and ladA genes have previously been reported to be also located on plasmids (OCT and pLW1071), corroborating their potential for horizontal transfer.…”
Section: Resultsmentioning
confidence: 99%
“…The branching pattern of these clades partially followed the taxonomic signal of the genomes they were retrieved from, specifically for most dominant phyla; however, some branches also contained alkB/M and ladA genes originating from different and distantly related phyla. The placement of phylogenetically diverse groups in one branch is likely to result from the horizontal transfer of these genes between microbial taxa [16]. Additionally, apart from the chromosomal type, both alkB/M and ladA genes have previously been reported to be located on plasmids (OCT and pLW1071), corroborating their potential for horizontal transfer.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, the homology of DNA sequences and organization of degrading genes carried by conjugative plasmids may be indicators that horizontal gene transfers can occur between HC-degrading bacteria during microbial adaptation to xenobiotics (Abbasian et al 2016). This is supported by in silico analysis, which demonstrated that HC-degrading genes alkB and catA can be subjected to horizontal transfer events among bacterial communities spreading the potential to degrade HCs (Rodrigues et al 2018). In an interesting study, Taghavi et al (2005) reported for the first time in planta horizontal gene transfer among plant-associated endophytic bacteria.…”
Section: Uptake and Degradation Of Hydrocarbons By Bacteriamentioning
confidence: 93%